Analysis The Development Marketing Strategy of Halal Tourism Facilities in Santen Island Banyuwangi Regency - Saifu din; Aunur Rofiq; Ahmad Djalaluddin (Islamic Economics Department, Faculty of Islamic Economics and Business, UIN SULTHAN THAHA SAIFUDDIN JAMBI, 2021)
The concept of halal tourism becomes a trend and provides opportunities for regions to develop the potential of tourism. One of them is the Banyuwangi Regency which has the potential for natural beauty and tries to develop tourist areas with the concept of halal tourism, especially on the Santen Island Banyuwangi. The purpose of this research is to describe the strategy for developing the halal tourism of Santen Island in terms of the facilities provided. The type of research used is qualitative with a descriptive approach. Data collection is obtained from interviews, observation, and documentation. The result of this study shows that the increase in internal facilities in Islamic tourism has been fulfilled from several aspects, such as separating the location of visits between men and women, building places of worship, regular notification of prayer times (azan), and the guarantee of halal food sold by traders.